2007
DOI: 10.1892/07-063.1
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Web-Based Health Survey of Retired Racing Greyhounds

Abstract: Background: Adoption of retired racing Greyhounds has become increasingly popular during the past decade. To date, research has focused on the physiologic and clinicopathologic peculiarities of Greyhounds but there is little published information on disease prevalence in the breed.Objective: The objective of this study is to determine the prevalence of disease in retired racing Greyhounds. Animals: In this study, 747 Greyhounds were used. Methods: A standardized survey method was used, and survey responses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…Recently, cardiovascular and thrombotic diseases and an increased frequency of hypocobalaminemia also have been described in Greyhounds. Furthermore, hyperhomocysteinemia in dogs with suspected chronic gastrointestinal disease is associated with hypocobalaminemia, which in turn has been linked to hypoalbuminemia .…”
mentioning
confidence: 99%
“…Recently, cardiovascular and thrombotic diseases and an increased frequency of hypocobalaminemia also have been described in Greyhounds. Furthermore, hyperhomocysteinemia in dogs with suspected chronic gastrointestinal disease is associated with hypocobalaminemia, which in turn has been linked to hypoalbuminemia .…”
mentioning
confidence: 99%
“…Lord and others (2007) calculated that neutering before adoption represents at least 15,000 surgeries a year. Considering that routine neutering in a RRG could result in haemostatic complications leading to readmission to the clinic, and in some cases, transfusion of blood or blood components, identifying the dogs at risk, or developing a simple protocol for prevention of this complication will be extremely valuable.…”
mentioning
confidence: 99%
“…Lord et al reported a high incidence of cancer in Greyhounds, the reasons for which are probably multifactorial 4. Some HETE isomers such as 5(S)HETE, 8(S)HETE, and 12(S)HETE have been implicated in promoting tumorigenesis and metastasis 21, 49, 50.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous and renal glomerular vasculopathy (CRGV) in Greyhounds is a form of thrombotic microangiopathy characterized by initial vascular lesions that include endothelial cell swelling, detachment, and microthrombosis 3. Interestingly, kidney disease accounts for approximately 8% of deaths in retired racing Greyhounds, with proteinuria and hypertension being common 4, 5…”
mentioning
confidence: 99%